Foreign direct investment inflows and financial development in Central and Eastern European Union countries: A panel cointegration and causality - Yilmaz Bayar; Marius Dan Gavriletea (International Journal of Financial Studies, 2018)
Foreign direct investment (FDI) inflows have increased considerably in the globalized world as of the mid-1980s. The main objective of this research is to analyze interactions between FDI inflows and financial sector development in Central and Eastern European Union countries between 1996 and 2015 with panel data analysis. Our findings reveal that there is no cointegrating relationship among FDI inflows, investments of foreign portfolio, and the development of financial sectors, but there is a one-way causality from development of financial sectors to FDI inflows over the short run.
Keywords: C22; F23; G10; O16; 330; financial development; foreign direct investment inflows; foreign equity investments; panel data analysis